Implementasi Awig-awig dalam Menjaga Kelestarian Subak Petung Desa Buruan Kecamatan Penebel Kabupaten Tabanan (Jurnal Agribisnis dan Agrowisata, 2025)
Implementation of Awig-awig in Maintaining the Preservation of Subak Petung, Buruan Village, Penebel District, Tabanan Regency. Subak Petung is one of the subaks in Hunting Village, Penebel District, Tabanan Regency and is currently experiencing the impact of land conversion which occurred due to the impact of the construction of boarding houses, shophouses, housing and others. As a result, agricultural land is decreasing due to agricultural land conversion activities. The data collection method uses in-depth interviews and documentation. The types of data used are quantitative data and qualitative data. The data sources used are primary data and secondary data. The data analysis method used is descriptive qualitative. The research results show that the implementation of awig-awig seen from the parhyangan aspect can be said to be very good, this can be seen from the religious ritual activities that are still routinely carried out today. The implementation of awig-awig seen from the pawongan aspect shows that awig-awig is still very well implemented which is related to resource mobilization and the search and distribution of irrigation water. The palemahan component contains awig-awig which regulates the prohibition of members from changing land functions. However, the awig-awig is not strong enough to suppress land conversion. Suggestions that can be recommended from this research include providing counseling to Subak Petung members regarding the importance of agriculture, especially rice field farming so as not to change the function of land.
Keywords: sustainability; awig-awig; subak; land conversion